Personality disorder & serious further offending - West, Laura (2014)
Offender characteristics are considered important in the prediction of future risk of re-offending and response to treatment. The psychiatric classification of offenders can therefore be an important variable influencing decision making. Although the relationship between personality disorder and offending is established in the literature, the relationship is complex.